2017
DOI: 10.1038/cti.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Altered regulatory T‐cell fractions and Helios expression in clinically isolated syndrome: clues to the development of multiple sclerosis

Abstract: Development of multiple sclerosis (MS) is frequently preceded by an acute or subacute neurological disturbance referred to as clinically isolated syndrome (CIS). The specific immunological disturbances present in CIS remain underexamined. This study analysed peripheral blood mononuclear cells from n=18 treatment-naive individuals with recently diagnosed CIS (<120 days) for disturbances in the phenotype of T regulatory (Treg), follicular T regulatory (Tfr), T helper (Th), follicular T helper (Tfh) and B cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 38 publications
(97 reference statements)
4
43
0
Order By: Relevance
“…A 4-h culture period is also the time popularly used for sensitive detection of cytokines that have accumulated intracellularly after blocking their secretion through the endoplasmic reticulum. 25 The differing levels of IL-10 mRNA in cells ex vivo were not replicated and suggested that during culture, an important external modulating agent was not present. Further, the potency of the modulating agent was highlighted as cells from MS patients now expressed higher IL-10 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4-h culture period is also the time popularly used for sensitive detection of cytokines that have accumulated intracellularly after blocking their secretion through the endoplasmic reticulum. 25 The differing levels of IL-10 mRNA in cells ex vivo were not replicated and suggested that during culture, an important external modulating agent was not present. Further, the potency of the modulating agent was highlighted as cells from MS patients now expressed higher IL-10 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of major (CD4 + T cells, CD8 + T cells, B cells, NK cells and monocytes) and numerically minor cell subsets (T reg cells, na€ ıve B cells, nonswitched memory B cells, switched memory B cells, CD56 lo CD16 hi NK cells, CD56 hi CD16 lo NK cells, classical monocytes, intermediate monocytes and nonclassical monocytes) were assessed by flow cytometry in freshly isolated PBMCs from HCs and CIS and MS patients as previously reported. 25,32 Serum levels (25(OH)D 3 ) were measured as previously described. 33…”
Section: T Cell B Cell Nk Cell and Monocyte Subset Analysis And VImentioning
confidence: 99%
“…71 Notwithstanding, in patients with early clinical phase clinically isolated syndrome, a neurological disturbance often occurs before the development of MS, and the proportions of cTfr cells and cTfh cells are not significantly different from healthy controls. 72 Specifically, proportions of proinflammatory Th17-like cTfr cells 15 and cytokine-producing CD45RA À Foxp3 lo non-cTfr cells 72 are increased, while the proportion of suppressive fraction CD45RA + Foxp3 lo resting cTfr cells 72 is reduced in MS patients, which may explain the impaired suppressive function of cTfr cells. This impairment may be because of a defect in CTLA-4 signalling and that the most potent Tfr cells home to the lymph organs to inhibit the ongoing GC response.…”
Section: Tfr Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…Systemic AIDs involve rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sjögren's syndrome (SS), ankylosing spondylitis (AS), IgG4‐related disease (IgG4‐RD) and common variable immune deficiency (CVID) . Organ‐specific AIDs involve multiple sclerosis (MS), myasthenia gravis (MG), Hashimoto's thyroiditis (HT), primary biliary cholangitis (PBC), type 1 diabetes (T1D) and ulcerative colitis (UC) . It is also demonstrated that when the regulatory capacity of Tfr cells is impaired, the expansion of Tfr cells is accompanied by the development of autoimmunity in mice …”
Section: Tfr Cells In Human Diseases and Animal Modelsmentioning
confidence: 99%
“…The composition of the immune system in CIS patients has been compared to healthy individuals or MS patients in several studies (11,12). One of these studies showed a lower proportion of a regulatory T cell (Treg) (CD45RA + FoxP3 lo ) and follicular T regulatory cell subsets (Tfr), in recently diagnosed untreated CIS patients when compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%